Radiation doses from computed tomography practice in Johor Bahru, Malaysia - Karim, M. K. A. (Elsevier Ltd, 2016)
Radiation doses for Computed Tomography (CT) procedures have been reported, encompassing a total of 376 CT examinations conducted in one oncology centre (Hospital Sultan Ismail) and three diagnostic imaging departments (Hospital Sultanah Aminah, Hospital Permai and Hospital Sultan Ismail) at Johor hospital's. In each case, dose evaluations were supported by data from patient questionnaires. Each CT examination and radiation doses were verified using the CT EXPO (Ver. 2.3.1, Germany) simulation software. Results are presented in terms of the weighted computed tomography dose index (CTDIw), dose length product (DLP) and effective dose (E). The mean values of CTDIw, DLP and E were ranged between 7.6±0.1 to 64.8±16.5mGy, 170.2±79.2 to 943.3±202.3mGycm and 1.6±0.7 to 11.2±6.5 mSv, respectively. Optimization techniques in CT are suggested to remain necessary, with well-trained radiology personnel remaining at the forefront of such efforts.